تأثيرالمنافسةعلى تطوربعض الصفات البدنية لدى لاعبي كرةالقدم أقل من 17 سنة - مامنية احمد; علايمية حنان (My University, 2025)
. ملخص الدراسة: جاءت الدراسة تحت عنوان تأثير المنافسة على تطوير الصفات البدنية لدى لاعبي كرة القدم صنف أشبال " هدف الدراسة: -التعرف على الانعكاسات البدنية التي تشملها المنافسة الرياضية المنتظمة والدائمة. - تسليط الضوء على قيمة المنافسة الرياضية بالنسبة للاعب كرة القدم. - إبراز سبب الفروقات البدنية بين لاعبي نفس الفريق. - مشكلة الدراسة: هل للمنافسة علاقة ارتباطية بتطوير الصفات البدنية لدى لاعبي كرة القدم (U17) صنف أشبال ؟ فرضيات الدراسة: -توجد علاقة ارتباطية بين المنافسة وتطوير صفة التحمل لدى لاعبي كرة القدم (U17) صنف اشبال. - توجد علاقة ارتباطية بين المنافسة وتطوير القوة الانفجارية لدى لاعبي كرة القدم (U17) صنف اشبال. - توجد علاقة ارتباطية بين المنافسة وتطوير صفة السرعة لدى لاعبي كرة القدم (U17) صنف اشبال. عينة الدراسة: قمنا باختيارها بالطريقة القصدية، وتمثلت في 12 لاعب أساسي و 12 لاعب احتياطيمن فريق أولمبي بومهرة من ولاية قالمة المشارك في رابطة عنابة الجهوية المنهج المتبع الدراسة تم استخدام المنهج الوصفي . ادوات الدراسة اختباراتات : demi . copper، اختبار الوثب العمودي من الثبات، اختبار 30م. النتائج المتوصل: -عدم وجود علاقة ارتباطية بين المنافسة وصفة التحمل لدى لاعبي كرة القدم صنف أشبال. عدم وجود علاقة ارتباطية بين المنافسة القوة الانفجارية لدى لاعبي كرة القدم صنف أشبال. - عدم وجود علاقة ارتباطية بين المنافسة واصفة السرعة لدى لاعبي كرة القدم صنف أشبال. الاقتراحات حث الطلبة والباحثين على جراء بحوث علمية مشابهة على نفس الفئة العمرية (الأشبال) على بقية البطولات بمختلف مستوياتها. - إدراك الرياضي لهامية ودور الانتظام في المنافسة الرياضية في رفع مختلف القدرات البدنية. خلق نوع من التنافس بيف جميع لاعبي الفريق من اجل اللعب بانتظام باعتبار المنافسة الرياضية هي احد اهم اسباب تنمية مختلف قد ارت لاعب كرة القدم. Abstract : The Impact of Competition on the Development of PhysicalAttributes in U17 Football Players. •Study Objectives - Identify the physical implications associatedwithregular and continuous participation in sportscompetitions. - Highlight the importance of sportscompetition for football players. - Explain the reasonsbehindphysical performance differencesamongplayers of the same team. ProblemStatement The study - seeks to answer the following question: Is there a correlationalrelationshipbetweencompetition and the development of physicalattributes in U17 football players? Hypotheses : Based on the problemstatement, the followinghypotheseswereformulated: 1. There is a correlationbetweencompetition and the development of endurance in U17 football players. 2. There is a correlationbetweencompetition and the development of explosive strength in U17 football players. 3. There is a correlationbetweencompetition and the development of speed in U17 football players . StudySample : The samplewasselectedintentionally and consisted of: - 12 startingplayers and 12 substitute playersfrom the Olympique Boumahra football club (Guelma Province), participating in the Annaba RegionalLeague. Methodology and Tools - MethodUsed: The descriptive methodwasadopted as itissuitable for the nature of thisstudy. - Measurement Tools: * Demi-Cooper Test to assess endurance. * Vertical Jump Test from a standing position to assess explosive strength. * 30-meter sprint test to assess speed •Results The studyyielded the followingresults: - No significantcorrelationwasfoundbetweencompetition and the development of endurance in U17 football players. - No significantcorrelationwasfoundbetweencompetition and the development of explosive strength. - No significantcorrelationwasfoundbetweencompetition and the development of speed. Recommendations and Suggestions - Encourage researchers and students to conductsimilarstudies on the sameagecategory (U17) acrossdifferentcompetitions and performance levels. - Promoteawarenessamongathletesregarding the importance of regular participation in sportscompetitions for enhancingphysicalcapabilities. - Foster internalcompetitionamong all team members to encourage consistent participation, as competitionis one of the keyfactors in developing a football player'sphysicalabilities. résumé : L’impact de la compétition sur le développement des attributs physiques en football U17 Joueurs. • Objectifs de l’étude - Identifier les implications physiques associées à une participation régulière et continue aux compétitions sportives. - Mettre en avant l’importance de la compétition sportive pour les joueurs de football. - Expliquez les raisons des différences de performance physique entre les joueurs d’une même équipe. Énoncé du problème L’étude - cherche à répondre à la question suivante : Existe-t-il une relation de corrélation entre la compétition et le développement des attributs physiques chez les joueurs de football U17 ? Hypothèses : Sur la base de l’énoncé du problème, les hypothèses suivantes ont été formulées : 1. Il y a une corrélation entre la compétition et le développement de l’endurance chez les joueurs de football U17. 2. Il y a une corrélation entre la compétition et le développement de la force explosive chez les joueurs de football U17. 3. Il y a une corrélation entre la compétition et le développement de la vitesse chez les joueurs de football U17. Échantillon d’étude : L’échantillon a été choisi intentionnellement et se composait de : - 12 joueurs titulaires et 12 joueurs remplaçants du club de football Olympique Boumahra (Province de Guelma), participant à la ligue régionale d’Annaba. Méthodologie et outils - Méthode utilisée : La méthode descriptive a été adoptée car elle est adaptée à la nature de cette étude. - Outils de mesure : * Test de Demi-Cooper pour évaluer l’endurance. * Test de saut vertical en position debout pour évaluer la force explosive. * Test de sprint de 30 mètres pour évaluer la vitesse • Résultats L’étude a donné les résultats suivants : - Aucune corrélation significative n’a été trouvée entre la compétition et le développement de l’endurance chez les joueurs de football U17. - Aucune corrélation significative n’a été trouvée entre la compétition et le développement de la force explosive. - Aucune corrélation significative n’a été trouvée entre la compétition et le développement de la vitesse. Recommandations et suggestions - Encourager les chercheurs et les étudiants à mener des études similaires sur la même catégorie d’âge (U17) dans différentes compétitions et niveaux de performance. - Sensibiliser les athlètes à l’importance de la participation régulière aux compétitions sportives pour améliorer leurs capacités physiques. - Favoriser la compétition interne entre tous les membres de l’équipe pour encourager une participation constante, car la compétition est l’un des facteurs clés du développement des capacités physiques d’un joueur de football.
-دراسةميدانيةفريقأولمبيبومهرةأحمد
Keywords: كرة القدم; المنافسة; لاعبين; صفات بدنية; مباريات; صنف أشبال; نادي هاوي; ملعب; competition; players; physical attributes; matches; junior category; amateur club; stadium; Football; compétition; joueurs; attributs physiques; matchs; catégorie junior; club amateur; stade